Advances in research on brain processing of food odors using different neuroimaging techniques. (December 2021) - Han, Pengfei
Abstract : Food odors play an important role in sensory and food perception as they affect the hedonic and motivational processes and determine food preference and consumption. Neuroimaging approaches have become increasingly important in understanding how the brain functions, providing a unique perspective in probing the perception and processing of food odors. This article presents an overview of the most recent research on brain processing of food odors, using the functional magnetic resonance imaging (fMRI), electroencephalography (EEG), or functional near-infrared spectroscopy (fNIRS). The implications and opportunities of neuroimaging in sensory and consumer sciences were discussed, while noting some important challenges and limitations. The review highlights the uniqueness of neuroimaging techniques in deepen our understanding of the food odor characteristics and the cognitive influences on food odor processing, that have potentials in research fields of sensory and consumer science.